Regulation of myogenesis and adipogenesis by the electromagnetic perceptive gene - Hwang, Jangsun; Jung, Hae Woon; Kim, Kyung Min; Jeong, Daun; Lee, Jin Hyuck; Hong, Jeong-Ho; Jang, Woo Young (Scientific reports, 2023)
Obesity has been increasing in many regions of the world, including Europe, USA, and Korea. To manage obesity, we should consider it as a disease and apply therapeutic methods for its treatment. Molecular and therapeutic approaches for obesity management involve regulating biomolecules such as DNA, RNA, and protein in adipose-derived stem cells to prevent to be fat cells. Multiple factors are believed to play a role in fat differentiation, with one of the most effective factor is Ca 2+ . We recently reported that the electromagnetic perceptive gene (EPG) regulated intracellular Ca 2+ levels under various electromagnetic fields. This study aimed to investigate whether EPG could serve as a therapeutic method against obesity. We confirmed that EPG serves as a modulator of Ca 2+ levels in primary adipose cells, thereby regulating several genes such as CasR, PPARγ, GLU4, GAPDH during the adipogenesis. In addition, this study also identified EPG-mediated regulation of myogenesis that myocyte transcription factors (CasR, MyoG, MyoD, Myomaker) were changed in C2C12 cells and satellite cells. In vivo experiments carried out in this study confirmed that total weight/ fat/fat accumulation were decreased and lean mass was increased by EPG with magnetic field depending on age of mice. The EPG could serve as a potent therapeutic agent against obesity.